The SDG and the environmental risk in the production of foliages in the province of Tequendama - Rojas Burgos, Efrén Eduardo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The article presents an analysis on the incorporation of the SDGs in the production of foliage and the chemical risk to which workers are exposed due to the use of agrochemicals in production, through a documentary review and an anova analysis. The objective focuses on the characterization of producers and the incorporation of the SDGs into the logistics processes of foliage production to mitigate the environmental impact. The research reflects that 83% of the population under study is unaware of the SDGs; hence, the importance of creating programs that train entrepreneurs in sustainable development